Ubiquitin-proteasome pathway in skeletal muscle atrophy - Pang, XiangSheng; Zhang, Peng; Chen, XiaoPing; Liu, WenMing (Frontiers in Physiology, 2023)
Skeletal muscles underpin myriad human activities, maintaining an intricate balance between protein synthesis and degradation crucial to muscle mass preservation. Historically, disruptions in this balance—where degradation overshadows synthesis—have marked the onset of muscle atrophy, a condition diminishing life quality and, in grave instances, imperiling life itself. While multiple protein degradation pathways exist—including the autophagy-lysosome, calcium-dependent calpain, and cysteine aspartate protease systems—the ubiquitin-proteasome pathway emerges as an especially cardinal avenue for intracellular protein degradation, wielding pronounced influence over the muscle atrophy trajectory. This paper ventures a panoramic view of predominant muscle atrophy types, accentuating the ubiquitin-proteasome pathway’s role therein. Furthermore, by drawing from recent scholarly advancements, we draw associations between the ubiquitin-proteasome pathway and specific pathological conditions linked to muscle atrophy. Our exploration seeks to shed light on the ubiquitin-proteasome pathway’s significance in skeletal muscle dynamics, aiming to pave the way for innovative therapeutic strategies against muscle atrophy and affiliated muscle disorders.